PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT UMUM BINA KASIH MEDAN - Sembiring, Elisabeth; Sinaga, Ria Veronika (UNIKA Santo Thomas, 2022)
The purpose of this study is to analyze the effect of service quality consisting of reliability, responsiveness, assurance, tangible, partial and simultaneous empathy on inpatient satisfaction at Bina Kasih General Hospital Medan. . The purpose of this study is expected to identify the problem of how the influence of service quality on patient satisfaction. This research method uses a sample of 96 respondents, data collection techniques through questionnaires and documentation and data analysis techniques with multiple regression. The results of the study using multiple linear regression equations: KP = 2.641 + 0.103K + 0.131Kt + 0.305Ky + 0.203B + 0.108E. This means that the variables of reliability, responsiveness, confidence, tangibles and empathy have a positive effect on patient satisfaction. The belief variable has a greater influence on inpatient satisfaction compared to other variables. The results of the F test indicate that the variables of reliability, responsiveness, confidence, tangibles and empathy have a simultaneous and significant effect on patient satisfaction, this can be seen from Fcount = 19,027 then H0 is rejected and H1 is accepted. The results of the t-test, showed that reliability, responsiveness, confidence, tangibles and empathy had a partial and significant effect on patient satisfaction, then H0 was rejected and H1 was accepted. The value of the determinant coefficient (R Square) is = r 0.514, which means that inpatient satisfaction can be explained by service quality variables (reliability, responsiveness, confidence, tangibles and empathy) of 51.4% while another 48.6% is explained by other factors that are not described in this study such as security, promotion and communication. The Bina Kasih Hospital Medan should improve the quality of service regarding the variables of reliability, responsiveness, confidence/guarantee, tangible, empathy in order to maintain the level of patient satisfaction for the future